Dido, Queen of Carthage and the Contradictions of Sovereignty - Edward Paleit (Journal of Marlowe Studies, 2025)
This essay argues that Marlowe's portrait of monarchy in Dido, Queene of Carthage both invites but ultimately defeats an attempt to read it directly through contemporary ideological contexts. While the play was written at a time of heightened debate surrounding the powers of princes, to which Dido herself gestures in a climactic moment of the action, the chief components of its idea of monarchy are rather the erotics of the gaze and a fantasy of self-sovereignty and illimitable autonomy. The former depends on, and probably derives from, the interaction between charismatic performers and an attentive audience within a playhouse, with the play both presuming and requiring that the boy-actor playing Aeneas is especially 'lovely' to look at, and blonde. The latter, contrastingly, possibly reflects an emerging discourse of political and especially monarchical sovereignty in the period, particularly in the wake of Jean Bodin's influential Six Livres de la République (1576), but translates the ideological into the personal and psychological in such a way as to defuse much of its political content or applicability. The collapse of the play's model of eroticised sovereign self-hood is highly traumatic, suggesting that it is rather a deeply invested fantasy than an attempt at subversion. Though highly distinctive, the play's understanding of monarchy occurs in many other works traditionally attributed to Marlowe and suggests his artistic influence on their composition, even if the extent to which he wrote the actual words, in the texts' final published form, can be disputed.